Construction of Donor–Acceptor Heterojunctions in Covalent Organic Framework for Enhanced CO2 Electroreduction. Issue 22 (5th November 2020) - Wu, Qiao; Mao, Min‐Jie; Wu, Qiu‐Jin; Liang, Jun; Huang, Yuan‐Biao; Cao, Rong
Abstract: Covalent organic frameworks (COFs) are promising candidates for electrocatalytic reduction of carbon dioxide into valuable chemicals due to their porous crystalline structures and tunable single active sites, but the low conductivity leads to unmet current densities for commercial application. The challenge is to create conductive COFs for highly efficient electrocatalysis of carbon dioxide reduction reaction (CO2 RR). Herein, a porphyrin‐based COF containing donor–acceptor (D–A) heterojunctions, termed TT‐Por(Co)‐COF, is constructed from thieno[3, 2‐b]thiophene‐2, 5‐dicarbaldehyde (TT) and 5, 10, 15, 20‐tetrakis(4‐aminophenyl)‐porphinatocobalt (Co‐TAPP) via imine condensation reaction. Compared with COF‐366‐Co without TT, TT‐Por(Co)‐COF displays enhanced CO2 RR performance to produce CO due to its favorable charge transfer capability from the electron donor TT moieties to the acceptor Co‐porphyrin ring active center. The combination of strong charge transfer properties and enormous amount of accessible active sites in the 2D TT‐Por(Co)‐COF nanosheets results in good catalytic performance with a high Faradaic efficiency of CO (91.4%, − 0.6 V vs reversible hydrogen electrode (RHE) and larger partial current density of 7.28 mA cm −2 at − 0.7 V versus RHE in aqueous solution. The results demonstrate that integration of D–A heterojunctions in COF can facilitate the intramolecular electron transfer, and generate high current densities for CO2 RR. Abstract : A donor–acceptor heterojunctions is constructed in cobalt porphyrin‐based COF (TT‐Por(Co)‐COF) to enhance the current density of CO2 electroreduction reaction due to its favorable charge transfer capability. TT‐Por(Co)‐COF nanosheets show a high FE CO of 91.4% at −0.6 V versus reversible hydrogen electrode (RHE) and large partial current density of 7.28 mA cm −2 at −0.7 V versus RHE in aqueous solution.